Claude Debussy : biographie critique suivie du catalogue de l'oeuvre - Lesure, François (Paris Fayard, 2003)
There's nothing romantic about Debussy's life: it's that of a creator who sacrificed almost everything to his work. Although it is generally accepted that his work paved the way for 20th-century music, his personality remains shrouded in shadow, as evidenced by the writings that have been devoted to him, due in particular to a relatively unstable private life. His life alternated between prosperous periods and moments of uncertainty, which can only be understood with the help of a rigorous chronology. The aim here is to present Debussy day by day, in the style of a chronicle, based on both his correspondence and the catalog of his works. By subtitling this book a “critical biography”, the author wishes to highlight this documentary effort and emphasize that the testimonies have been called into question. He thus discusses the “impressionist” label so often attributed to Debussy, emphasizing all that the composer owes to symbolism. As for the works, their genesis and distribution, they are placed in the context of the musician's life, with particular attention paid to the interpreters and what we can assume of the interpretation they underwent and sometimes endured. The many projects he worked on have also been taken into account, to better grasp the progression of his intentions and hopes, as well as the delays they implied for his other scores. In addition, the reception of his works has been taken into account, enabling our readers to follow the slow penetration of his most innovative compositions, and the reasons for the rejection or incomprehension of many critics, both in France and, as far as possible, abroad. Finally, an analysis of the press has made it possible to determine the extent to which he was involved - voluntarily or involuntarily - in the quarrels of his time. The catalog raisonné of the composer's works, entirely revised and updated, completes this biography.
Keywords: Debussy, Claude -- 1862-1918; 19th Century (1801-1900); 20th Century (1901-2000); Composer; Biography